Identification of suitable methods in handling research in urban park design for the elderly in Kuala Lumpur: a systematic literature review - Hilaluddin, Raudhah; Hussain, Norhuzailin; Maruthaveeran, Sreetheran; Mohd Yusof, Mohd Johari (Human resource management academic research society, 2022)
Recognizing the importance of population aging and urbanisation research in achieving healthy ageing in cities, the United Nations (UN) conducts continuing initiatives to ensure healthy lives and promote well-being for people of all ages. Malaysia's population ageing has concentrated on the elderly and all areas of their well-being as the country aspires to become a developed nation by 2040. In the planning and design of urban environments, there is a critical requirement for adoptive social comfort among the elderly. User-centered design for the elderly is more complex than for other user groups. Researchers must be aware of the behaviors, sensory and cognitive abilities, and attitudes of the elderly when conducting the study. To address this issue, this study’s objective is to explore and analyse the existing methods and tools used in urban park study among the elderly. To meet the study's goals, the researcher should employ practical approaches. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method published in 2009. The authors used Science Direct and an archival Scopus database to manage the search results and systematically reviewed existing literature on the elderly in the urban park. Keywords related to "elderly and urban parks design" were examined in articles published between 2016 and 2021. Resulting in 31 relevant papers, the methods used have been analysed, and the effective way to be used in handling research in urban park design for the elderly in Kuala Lumpur. This article was to combine field observation and interviews with users and experts.